In the realm of gods and kings arts of India - Topsfield, Andrew (Philip Wilson Publishers Distributed in North America by Palgrave Macmillan, 2013)
"This corrected and updated volume celebrates the wealth and diversity of the arts of India created for the life of courts and temples from 1000 bc to twentieth century, 112 paintings, 59 objects and 21 photographs ranging in date from the second century bc to the late twentieth century reflect the variety and continuities of India's aesthetic traditions." -- Provided by publisher